Tax policy response to support taxpayers in the face of the repercussions of the pandemic (Covid 19) - Zaouak, El haoues (Journal of Human Sciences, 2021)
The study attempted to shed light on how tax policy responded to support taxpayers in the face of the economic consequences of the pandemic (Covid 19). Tax authorities had to step in and adapt their legislation to the situation caused by the epidemic, and take sound measures aimed at mitigating the impact on people affected by the epidemic and helping them restore their productive capacity and enabling them to meet tax obligations.      The study concluded that despite the rapid response of tax policy to support taxpayers, the epidemic imposed a new logic in tax legislation, requiring the suspension of the tax base, and the application of urgent measures that in many cases violate the usual tax rules.